Digital Business-Based Financing in Islamic Educational Institutions: A Systematic Literature Review - Huda, Akhmad; Jazariyah, Ita (PenaEmas, 2025)
Abstrak This study aims to systematically examine the basic concept of digital-based Islamic education financing, the potential of the digital economy in the modern era, implementation strategies, and the challenges and solutions faced in its development. The method used was a systematic literature review of 18 national and international scientific journal articles published in the last five years (2019–2024). The results show that the digitalization of Islamic education financing is realized through various forms such as Islamic fintech, zakat crowdfunding, Islamic peer-to-peer lending, and the development of digital business units by educational institutions. The potential of the digital economy is proven to be large by the use of social media platforms, e-commerce, and digital-based Islamic content as alternative financing sources. Strategies used include integrating a digital entrepreneurship curriculum, strengthening human resource capacity, developing technological infrastructure, and collaborating with Islamic financial institutions and digital Muslim communities. Challenges faced include limited infrastructure, low digital literacy, and resistance to innovation. This study concludes that digital entrepreneurship is a transformative and sustainable financing alternative for Islamic educational institutions. This research also provides practical recommendations in the form of digital entrepreneurship curriculum integration, digital literacy training, the establishment of sharia-based business units, and national policy support. Kata Kunci: Islamic education financing, digital business, digital economy, sharia fintech, systematic literature Abstract Penelitian ini bertujuan untuk mengkaji secara sistematis konsep dasar pembiayaan pendidikan Islam berbasis usaha digital, potensi ekonomi digital di era modern, implementasi strategi, serta tantangan dan solusi yang dihadapi dalam pengembangannya. Metode yang digunakan adalah studi literatur sistematis (Systematic Literature Review) terhadap 18 artikel jurnal ilmiah nasional dan internasional yang diterbitkan dalam kurun waktu lima tahun terakhir (2019–2024). Hasil penelitian menunjukkan bahwa digitalisasi pembiayaan pendidikan Islam terwujud melalui berbagai bentuk seperti fintech syariah, crowdfunding zakat, peer-to-peer lending syariah, dan pengembangan unit usaha digital oleh lembaga pendidikan. Potensi ekonomi digital terbukti besar dengan pemanfaatan platform media sosial, e-commerce, serta konten Islami berbasis digital sebagai sumber pembiayaan alternatif. Strategi yang digunakan mencakup integrasi kewirausahaan digital, penguatan kapasitas SDM, pengembangan infrastruktur teknologi, serta kolaborasi dengan lembaga keuangan syariah dan komunitas Muslim digital. Tantangan yang dihadapi meliputi terbatasnya infrastruktur, rendahnya literasi digital, dan resistensi terhadap inovasi. Penelitian ini menyimpulkan bahwa usaha digital merupakan alternatif pembiayaan yang transformatif dan berkelanjutan bagi lembaga pendidikan Islam. Penelitian ini juga memberikan rekomendasi praktis berupa integrasi iklim kewirausahaan digital, pelatihan literasi digital, pembentukan unit usaha berbasis syariah, dan dukungan kebijakan nasional. Keywords: pembiayaan pendidikan Islam, usaha digital, ekonomi digital, fintech syariah, literatur sistematis.